Sustainable Mixed Cropping Systems for the Boreal-Nemoral Region - Lizarazo, Clara I.; Tuulos, Antti; Jokela, Venla; Mäkelä, Pirjo S. A. (Frontiers in Sustainable Food Systems, 2020)
Mixed cropping, including intercropping, is the oldest form of systemized agricultural production and involves the growing of two or more species or cultivars of the same species simultaneously in the same field. However, mixed cropping has been little by little replaced by sole crop systems, especially in developed countries. Some of the advantages of mixed cropping are, for example, resource use efficiency and yield stability, but there are also several challenges, such as weed management and competition. The boreal-nemoral region lies within the region 55 to 70°N. In this area, for example in Finland, the length of the thermal growing season varies from >105 to over 185 days. Typically, variation between locations and years is marked. However, during the year, there can be a wide range of temperature extremes between −70 and +30°C. The majority of cropping systems in this region are usually monocultures, except for forage grass mixtures. The possibility of having several crops in a mixture is very challenging in the region due to the short growing season and extreme cold temperatures, meaning that crop earliness and overwintering capacity are a considerable restriction for year-round mixed cropping. A further restriction is the quality requirements set by the industry. Our review will explore a range of mixed cropping possibilities for the boreal-nemoral region, including different possible combinations of spring, winter, perennial, biennial, catch, and cover crops. The reviewed mixed cropping systems could considerably improve the sustainability and efficiency of crop production.